2020
DOI: 10.1186/s12917-020-02600-3
|View full text |Cite|
|
Sign up to set email alerts
|

Are the energy matrix values of the different feed additives in broiler chicken diets could be summed?

Abstract: Background The aim of this study is to investigate whether the energy matrix values of the nonstarch polysaccharide- (NSP-) degrading enzymes, bioemulsifier (LYSOFORTE®), guanidinoacetic acid (CreAMINO®), or their combinations could be summed. The effects of these additives on the growth performance, carcass traits, and economic value of the broiler chicken diets were evaluated. A total of 525-one-day-old Ross chicks with an initial body weight of 42.96 ± 0.87 g were haphazardly allocated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Better utilization and decreased fecal energy losses were reported from unsaturated fats compared to those from saturated fats. This resulted in an increased ME for the unsaturated fats [42][43][44][45] and additional energy utilization [46]. An expected higher fat deposition was observed due to the increased triglyceride storage in the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Better utilization and decreased fecal energy losses were reported from unsaturated fats compared to those from saturated fats. This resulted in an increased ME for the unsaturated fats [42][43][44][45] and additional energy utilization [46]. An expected higher fat deposition was observed due to the increased triglyceride storage in the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These components also reduce the negative effect of environmental stressors on the immune systems and production standards of an animal. Thus, in animal nutrition, the focus is on competitive exclusion, antibacterial peptides, prebiotics, probiotics, yeasts, and other additives [1][2][3]. These additives, which can be supplemented to chickens and piglets feed, are medium-chain fatty acids (MCFAs).…”
Section: Introductionmentioning
confidence: 99%
“…Lysoforte (LFT), a lysolecithin produced from lecithin that acts as an efficient emulsifier, could improve poultry growth, reproduction, and carcass quality by enhancing nutrient digestion and absorption, as well as reducing their mortality. In broiler chickens, LFT supplementation elevated average daily gain (ADG), final body weight, relative growth rate, dressing percent, carcass quality, net profit, total return, economic efficiency, and reduced energy matrix value, FCR, and mortality rate ( 4 , 5 ). Previous research has shown that LFT supplementation increased saturated fatty acids absorption.…”
Section: Introductionmentioning
confidence: 99%